The Schulthess local Shoulder Arthroplasty Registry (SAR): cohort profile. Issue 11 (26th November 2020) - Marzel, Alex; Schwyzer, Hans-Kaspar; Kolling, Christoph; Moro, Fabrizio; Flury, Matthias; Glanzmann, Michael C; Jung, Christian; Wirth, Barbara; Weber, Beatrice; Simmen, Beat; Scheibel, Markus; Audigé, Laurent
Abstract : Purpose: Clinical registries are essential for evaluation of surgical outcomes. The Schulthess Shoulder Arthroplasty Registry (SAR) was established in 2006 to evaluate safety, function, quality-of-life and patient satisfaction in patients undergoing shoulder arthroplasty. Participants: Adult patients undergoing anatomic or reverse shoulder joint replacement at the Schulthess Klinik, a high-volume, leading orthopaedic surgery centre in Zürich, Switzerland. Findings to date: Between March 2006 and December 2019, the registry covered 98% of eligible operations. Overall, 2332 patients were enrolled with a total of 2796 operations and 11 147 person-years of follow-up. Mean age at baseline was 71 (range: 20–95), 65% were women. Most common indication was rotator cuff tears with osteoarthritis (42%) and the mean preoperative Constant Score was 31 (±15). The most frequent arthroplasty type was reverse, increasing from 61% in 2006–2010 to 86% in 2015–2019. Functional recovery peaked at 12-month postoperatively and did not show a clinically relevant deterioration during the first ten follow-up years. Since its establishment, the registry was used to address multiple pertinent clinical and methodological questions. Primary focus was on comparing different implant configurations (eg, glenosphere diameter) and surgical techniques (eg, latissimus dorsi transfer) to maximise functional recovery. Additionally, the cohort contributed to the determination of the clinical relevance and validity of radiological monitoring of cortical bone resorption and scapular notching. Finally, SAR data helped to demonstrate that returning to sports was among key patient expectations after reverse shoulder arthroplasty. Future plans: As first patients are approaching the 15 years follow-up landmark, the registry will continue providing essential data on long-term functional outcomes, implant stability, revision rates and aetiologies as well as patient satisfaction and quality-of-life. In addition to research and quality-control, the cohort data will be brought back to the patients by bolstering real-time clinical decision support.